THREE-DIMENSIONAL ADJUSTING DEVICE DESIGN AND FINITE ELEMENT ANALYSIS - LI ChunGuang; XIN ZhiJie; ZHANG Jin (Jixie qiangdu)
Through the analysis of working condition of three-dimensional adjusting frame,I perform theoretical calculations and choose the main components of three-dimensional adjusting frame. And I make a overall design of the mechanical structure of three-dimensional adjusting frame from top to down by using the software of UG NX. Then under the circumstance of ANSYS Workbench I complete the static analysis and modal analysis of three-dimensional adjusting frame,and got the overall deformation under their own gravity and first six order natural frequency and vibration mode. The results show that this design of threedimensional adjusting frame has the high stiffness and dominant frequency is lower than vibration frequency of the source and can effectively avoid the vibration of source.